Santer Application for Fulfillment of Access to Public Services in Samarinda City - Christover, Deandlles; Irawan, Bambang; Akbar, Paisal; Ibrahim, Adil Hassan; Ananda, Alfin (Jurnal Studi Ilmu Pemerintahan, 2023)
The internet revolution has brought significant transformation to the government in providing services to the public. Since the 1990s, governments worldwide have launched projects to simplify the service delivery process through electronic means. These channels are known as E-government or electronic government. One form of E-Government transformation provided by the City Government of Samarinda is by presenting the SANTER application. SANTER stands for One Integrated Application, an embodiment of E-Government in supporting applications for the City of Samarinda. The SANTER application, which is still being developed, needs to improve its features according to the needs of public services. One way to get a complete picture of how this application has been running is to research the various features provided and interpret the results to give an in-depth description of the utilization of the services offered. The method used in this research is qualitative. Data was collected through the trial process of the SANTER application, which was carried out jointly by 51 students of the Information Systems & E-Government course at the Faculty of Social and Political Sciences, Widya Gama Mahakam University, Samarinda. The research findings show an overview of the application, the available features, and the advantages and disadvantages of the SANTER application. Based on the processed results of this research data, it can be concluded that the SANTER application is still not maximal in providing the services the community wants.